Social identity - Jenkins, Richard, 1952- (London ; New York : Routledge, 2004)
Developing the argument that identity is both individual and collective, the author explores the work of major social theorists such as Mead, Goffman and Barth to explain the experience of identity in everyday life
Acknowledgements -- Knowing who's who -- A sign of the times? -- Understanding identification -- Selfhood and mind -- Embodied selves -- Entering the human world -- Self-image and public image -- Groups and categories -- Beyond boundaries -- Symbolising belonging -- Predictability -- Institutionalising identification -- Organising identification -- Categorisation and consequences -- Why identity matters in the modern world
Includes bibliographical references (pages [184]-209) and index
Keywords: Group identity